2017
DOI: 10.1093/cercor/bhx302
|View full text |Cite
|
Sign up to set email alerts
|

Basal Forebrain Gating by Somatostatin Neurons Drives Prefrontal Cortical Activity

Abstract: The basal forebrain provides modulatory input to the cortex regulating brain states and cognitive processing. Somatostatin-expressing neurons constitute a heterogeneous GABAergic population known to functionally inhibit basal forebrain cortically projecting cells thus favoring sleep and cortical synchronization. However, it remains unclear if somatostatin cells can regulate population activity patterns in the basal forebrain and modulate cortical dynamics. Here, we demonstrate that somatostatin neurons regulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 68 publications
4
26
0
Order By: Relevance
“…However, we consider that the enhancement of quiet wakefulness triggered by DBS may be due to the activation of GABAergic BF circuits. This is consistent with observations in the BF nucleus ventral pallidum, where optogenetic inhibition of SST GABAergic neurons triggers transitions from quiet wakefulness to exploratory behavior as well as enhances running speed (Espinosa et al, 2019a(Espinosa et al, , 2019b. Available evidence thus points to an important role for BF GABAergic circuits in triggering DMN-type behaviors, with grooming and quiet wakefulness possibly involving preferential recruitment of PV and SST GABAergic populations.…”
Section: Bf Electrical Stimulation Modulates Neuropeptide Levels Withsupporting
confidence: 89%
“…However, we consider that the enhancement of quiet wakefulness triggered by DBS may be due to the activation of GABAergic BF circuits. This is consistent with observations in the BF nucleus ventral pallidum, where optogenetic inhibition of SST GABAergic neurons triggers transitions from quiet wakefulness to exploratory behavior as well as enhances running speed (Espinosa et al, 2019a(Espinosa et al, , 2019b. Available evidence thus points to an important role for BF GABAergic circuits in triggering DMN-type behaviors, with grooming and quiet wakefulness possibly involving preferential recruitment of PV and SST GABAergic populations.…”
Section: Bf Electrical Stimulation Modulates Neuropeptide Levels Withsupporting
confidence: 89%
“…Numerous evidences indicated that GABA SOM neurons contain diverse regional populations and functions in the BF. GABA SOM neurons in VP of BF regulate local gamma oscillations to drive prefrontal cortical activity 39,40 . In sleep–wake cycle, BF GABA SOM neurons exert a sleep promoting effect, 10 and the synthetic SOM analog, octreotide, can either suppress NREM sleep or increase REM sleep 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, gamma-band activity in DMN areas is elevated during periods of quiet wakefulness and is transiently suppressed during the performance of cognitive tasks ( Miller et al., 2009 ; Ossandon et al., 2011 ). It has been suggested that GABAergic cells, in particular somatostatin-expressing cells, or the glutamatergic cells in the BFB mediate the generation and coordination of these gamma oscillations ( Espinosa et al., 2019a , 2019b ; Yang et al., 2017 ). In our study, analysis of the low-frequency fluctuations in the BOLD signal revealed decreased FC and resting-state neural activity in cortical DMLN region upon stimulation of BFB cholinergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ACh enhances visual processing by inducing cortical decorrelation and desynchronization in sensory cortices, which increases the signal to noise ratio ( Chen et al., 2015 ; Nguyen et al., 2015 ; Pinto et al., 2013 ). Moreover, the BFB has been implicated in cortical network switching between brain states by exerting direct and/or indirect control to the prefrontal cortex ( Espinosa et al., 2019b ; Li et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%